The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1111/tri.12688
|View full text |Cite
|
Sign up to set email alerts
|

CD25 blockade in kidney transplant patients randomized to standard-dose or high-dose basiliximab with cyclosporine, or high-dose basiliximab in a calcineurin inhibitor-free regimen

Abstract: SummaryAn increased basiliximab dose may saturate T-cell CD25 receptors in kidney transplant patients receiving calcineurin inhibitor (CNI)-free immunosuppression. In a 12-week study, 16 de novo kidney transplant patients were randomized to (i) 40 mg basiliximab with cyclosporine [n = 3] (controls), (ii) 80 mg basiliximab with cyclosporine [n = 6], or (iii) 80 mg basiliximab with everolimus (CNI-free) [n = 7], all with mycophenolic acid and steroids. Recruitment was stopped prematurely due to increased biopsy-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 32 publications
(58 reference statements)
2
15
0
1
Order By: Relevance
“…We performed sensitivity analysis excluding 2 trials [22, 35] that reported GFR estimates based on MDRD and a similar effect to the original meta analysis was observed (MD, 5.18; 95% CI, 2.07–8.30; I 2 , 56%). We performed additional sensitivity analysis excluding 2 trials [19, 24] that did not specify just which methods used to estimate GFR and a similar effect to the original meta analysis was observed (MD, 6.30; 95% CI, 3.06–9.53; I 2 , 42%).…”
Section: Resultsmentioning
confidence: 83%
See 3 more Smart Citations
“…We performed sensitivity analysis excluding 2 trials [22, 35] that reported GFR estimates based on MDRD and a similar effect to the original meta analysis was observed (MD, 5.18; 95% CI, 2.07–8.30; I 2 , 56%). We performed additional sensitivity analysis excluding 2 trials [19, 24] that did not specify just which methods used to estimate GFR and a similar effect to the original meta analysis was observed (MD, 6.30; 95% CI, 3.06–9.53; I 2 , 42%).…”
Section: Resultsmentioning
confidence: 83%
“…After examining the titles and abstracts and eliminating identical publications, 67 possibly qualified articles were determined. Fifteen reports [2236] of 11 trials, including a total of 1,633 randomized patients, were chosen for inclusion in the meta-analysis (Fig 1). One of these trials was available in abstract form only by Wolfgang et al 2012 [31].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The absence of first-order elimination term lead to apparent VM and KM values that may be superior than "actual" values. In studies where KM was not identifiable, either KM value was fixed to low values,as done for brodalumab [77] (anti-IL-17R) and dupilumab [78] (IL-4Rα), with values of 0.02 and 0.01 mg/L, respectively, or the Michaelis-Menten term was replaced by a zero-order elimination rate constant, as done for cetuximab [79,80] and basiliximab [81] (anti-CD25). However, MichaelisMenten models allow a quantification of the relationship between antigen mass and pharmacokinetic parameters only if antigen mass is added as a covariate on Michaelis-Menten term parameters.…”
Section: Michaelis-menten Modelmentioning
confidence: 99%